Use of Artificial Intelligence in Analyzing Brand Engagement and Customer Experience to Support Sustainability - Hamidah Tussifah; Gina Atikah Hasni; Adzimatinoor Nabila Rahmadania (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Artificial intelligence is highly influential in the economic development of the millennial generation. Brand engagement is strategic in brand building, and as customer expectations continue to rise, improving customer experience has become a challenge for businesses. In this rapid development, businesses must continue to innovate in order to improve their business. The utilization of AI in various aspects of business requires various business strategies in its development. This article aims to analyze the benefits of AI in the context of brand engagement and customer experience to support sustainability. We present a comprehensive literature review on this topic. The results of this study show that Artificial Intelligent has an effect on analyzing brand engagement and customer experience to support sustainability.